Business – process for investment activity - Samson Darchia (Financial Markets, Institutions and Risks)
This paper summarizes the arguments and counterarguments within the scientific discussion on the issue about the activity of financial director in the sphere of investment. The main purpose is to сonduct research about investment activities, the design of business processes, to evaluate and find improvements that help to organize business process. Business-process is based on the circumstances, that the financial director is responsible for the company’s money and investments one of the important components of the mentioned cash flow. In the given article the high-level business process of investment activity is offered, also there are given pre-investment and investment budgeting sub-processes. The author proposes to distinguish three phases: Pre-investment, investment, exploitation. Improvements in business process are perceived by members of companies and directors, finance departments as one of the main factors in improving the quality of investment activity. The results of the study can be useful for business managers in the context of developing improvement measures in investment activity, identifying key areas for improving the business process, which will improve profitability, transparency of financial activities, and trust and willingness to cooperate with investors in the future.